The Study of Procrastination Behavior Effected Performance at Workplace of Municipality Staff - Nawakitrangsan, Napatchanan; Wongpinpetch, Pinkanok; Chunin, Manop (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2022)
This research aimed to study the procrastination behavior at work in municipality office as the components of procrastination behavior created by Chu and Choi (2005). A mixed methods research was used. A qualitative research was used with a semi-structure and an in-depth interviewed 12 key persons in municipality office. A quantitative research method was used with a stratified random sample of 212 municipality staff from municipality office in Nakhon Pathom province, Nonthaburi province and Rangsit City. The questionnaire asking about the procrastination behavior with reliability of .904 was used to collect the data. Confirmatory factor analysis used. The results of this research found that: the components of the procrastination behavior at work of municipality staff consisted of two factors; passive procrastination behavior and active procrastination behavior. The model of the procrastination behavior at work of municipality staff was found to accord with empirical data. Chi-square goodness of fit test value was 52.824 with 42 degrees of freedom, p=.122, CFI=.996, Tuker-Lewis Index (TLI) = .993, SRMR = .033 and RMSEA=.028. These factors can be used as a guide for creating and setting all activities to activate the procrastination behavior in the way that lead to best manner of municipality staff in the workplace in the future.